Effect of Roofing Materials on Hemato-Biochemical, Hormonal and Antioxidant Profile of Sheared and NonSheared Sheep - Khant, Malhar; Modi, Rakesh J; Patel, Nitin R; Wadhwani, Kishan N; Pathan, Mohsin M (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The effect of roofing material on hemato-biochemical, hormonal and antioxident parameters of sheared and non-sheared sheep was invastigated. Twenty four adult dry indigenous sheep were distributed randomly on the basis of body weight (20-35 kg) into two roof treatment groups, i.e., T1: asbestos roof and T2: agronet roof. Each treatment comprised of six sheared and six non-sheared animals. Hemoglobin (g/dL) and PCV (%) concentrations of sheep were comparable between roof treatments and between shearing practices. Serum glucose level was significantly (p <0.05) higher in sheared and non sheared sheep reared under asbestose roof (44.76 ± 0.31, 45.29 ± 0.31 mg/dl) than the agronet roof shelter (43.78 ± 0.31, 43.46 ± 0.33 mg/dl). Serum uric acid level was significantly (p <0.05) decreased in sheared animals reared under agronet roofed shelter as compared to non-sheared animals reared under abstestos roofed shelter (0.41 ± 0.05 vs. 0.55 ± 0.06 mg/dL). Serum urea and creatinine levels of sheared sheep were lower than non-sheared ones under both the roofing materials with significant difference only in creatinine. The serum levels of hormone T3 and cortisol were statistically similar between roof treatments and shearing practices, whereas serum T4 was significantly (p <0.05) higher in sheared animals (37.19 ± 3.17 ng/ml) reared under asbestos roofed shelter compared to agronet. Glutathione peroxidase activity was increased significantly (p <0.05) in sheared and non-sheared animals reared under asbestos roofed shelter, whereas superoxide dismutase activity decreased significantly (p <0.05) in sheared animals under agronet roof (5.73 ± 0.27 U/ml). However, lipid hydroperoxide, catalase and heat shock protein 70 activity were neither influenced significantly by roofing materials nor by shearing practices. The results indicated the role of effective roofing material of shelter and shearing plans in reducing the effect of heat stress on sheared and unsheared sheep.